The language and folklore of West Sakhalin Ainu - A re-edition of Murasaki Kyōko's 'Karafuto Ainugo' with translation and grammatical notes - Elia Dal Corso (Lincom Publishing, 2021)
This book is a re-edition of Kyōko Murasaki’s カラフトアイヌ語 – 資料 (Karafuto ainugo – Shiryō) (The Karafuto Ainu language – Texts) and カラフトアイヌ語 – 文法篇 (Karafuto ainugo – Bunpō hen) (The Karafuto Ainu language – Grammar), published in 1976 and 1979 respectively by Kokushokan Kōkai. The two volumes are the result of 11 years of fieldwork in Tokoro (常呂), a small town on the northern coast of Hokkaidō that faces the Okhotsk Sea, about 30 kilometers west of Abashiri. In Tokoro, Kyōko Murasaki worked with two of the last native speakers of Sakhalin Ainu, Haru Fujiyama and Yuk Ōta.